Diversity of Mobile Genetic Elements in the Mitogenomes of Closely Related Fusarium culmorum and F. graminearum sensu stricto Strains and Its Implication for Diagnostic Purposes - Kulik, Tomasz; Brankovics, Balazs; van Diepeningen, Anne D.; Bilska, Katarzyna; Żelechowski, Maciej; Myszczyński, Kamil; Molcan, Tomasz; Stakheev, Alexander; Stenglein, Sebastian; Beyer, Marco; Pasquali, Matias; Sawicki, Jakub; et al. (Frontiers in Microbiology, 2020)
Much of the mitogenome variation observed in fungal lineages seems driven by mobile genetic elements (MGEs), which have invaded their genomes throughout evolution. The variation in the distribution and nucleotide diversity of these elements appears to be the main distinction between different fungal taxa, making them promising candidates for diagnostic purposes. Fungi of the genus Fusarium display a high variation in MGE content, from MGE-poor (F. oxysporum and Fusarium fujikuroi species complex) to MGE-rich mitogenomes found in the important cereal pathogens F. culmorum and F. graminearum sensu stricto. In this study, we investigated the MGE variation in these latter two species by mitogenome analysis of geographically diverse strains. In addition, a smaller set of F. cerealis and F. pseudograminearum strains was included for comparison. Forty-seven introns harboring from 0 to 3 endonucleases (HEGs) were identified in the standard set of mitochondrial protein-coding genes. Most of them belonged to the group I intron family and harbored either LAGLIDADG or GIY-YIG HEGs. Among a total of 53 HEGs, 27 were shared by all fungal strains. Most of the optional HEGs were irregularly distributed among fungal strains/species indicating ancestral mosaicism in MGEs. However, among optional MGEs, one exhibited species-specific conservation in F. culmorum. While in F. graminearum s.s. MGE patterns in cox3 and in the intergenic spacer between cox2 and nad4L may facilitate the identification of this species. Thus, our results demonstrate distinctive traits of mitogenomes for diagnostic purposes of Fusaria.